Intuitive Feelings of Warmth and Confidence in Insight and Noninsight Problem Solving of Magic Tricks - Hedne, Mikael R.; Norman, Elisabeth; Metcalfe, Janet (Frontiers in Psychology, 2016)
The focus of the current study is on intuitive feelings of insight during problem solving and the extent to which such feelings are predictive of successful problem solving. We report the results from an experiment (N=51) that applied a procedure where the to-be-solved problems were 32 short (15 s) video recordings of magic tricks. We included metacognitive ratings similar to the "warmth ratings" previously used by Metcalfe and colleagues, as well as confidence ratings. At regular intervals during problem solving, participants indicated the perceived closeness to the correct solution. Participants also indicated directly whether each problem was solved by insight or not. We found that problems that people claimed were solved by insight were characterised by higher accuracy and higher confidence than noninsight solutions. There was no difference between the two types of solution in warmth ratings, however. Confidence ratings were more strongly associated with solution accuracy for noninsight than insight trials. Moreover, for insight trials the participants were more likely to repeat their incorrect solutions on a subsequent recognition test. The results have implications for understanding people's metacognitive awareness of the cognitive processes involved in problem solving. They also have general implications for our understanding of how intuition and insight are related.